Essays on sugarcane - Jacomini, Rafael Lopes (2017)
This thesis contains an introduction followed by two independent chapters, each of them dealing with a different empirical issue of Brazilian sugarcane sector. The aim of the study in chapter 2 is the productivity of São Paulo state sugarcane mills in the post-2008 period. To evaluate the productivity changes a total factors productivity (TFP) approach combined with stochastic frontier models were used and then the TFP growth between 2010 and 2015 had been decomposed into four components: technical progress; change in technical efficiency; change in the production scale and change in the allocative efficiency. The results seem to be consistent and indicate an efficiency loss for the mills over the analyzed period, as well highlighted the importance of capital for the mills, indicating that financial problems can lead to productivity losses in this sector. Chapter 3 presents an analyze the existence of asymmetric price transmission between producers and retail markets for refined sugar at the State of Sao Paulo, considering aspects such as direction, magnitude and speed of price transmissions. The empirical analysis used monthly averages of prices for the period from May 2003 to February 2015 and the results suggest that the transmission of shocks is bidirectional. Formal tests suggest that the hypothesis of symmetry in price transmission both in the short and long-run from retail to producers cannot be rejected.